2015
DOI: 10.1093/pcp/pcv021
|View full text |Cite|
|
Sign up to set email alerts
|

Base to Tip and Long-Distance Transport of Sodium in the Root of Common Reed [Phragmites australis (Cav.) Trin. ex Steud.] at Steady State Under Constant High-Salt Conditions

Abstract: We analyzed the directions and rates of translocation of sodium ions (Na(+)) within tissues of a salt-tolerant plant, common reed [Phragmites australis (Cav.) Trin. ex Steud.], and a salt-sensitive plant, rice (Oryza sativa L.), under constant high-salt conditions using radioactive (22)Na tracer and a positron-emitting tracer imaging system (PETIS). First, the test plants were incubated in a nutrient solution containing 50 mM NaCl and a trace level of (22)Na for 24 h (feeding step). Then the original solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…As will be seen later, SOS1 activity is very important for K + uptake, especially under low-K + conditions. Recently, it has been consistently shown that the difference between tolerant reed and sensitive rice is due to the difference in ability to reduce transport of Na + to the shoot; only the reed plants restricted Na + transport to the shoot base while the rice plants lacked this capacity (Fujimaki et al, 2015). This restriction was shown to involve Na + retrieval from the xylem and recirculation to the soil through the phloem.…”
Section: Resistance To Radial Transport and Xylem Loading Of Na+mentioning
confidence: 99%
See 2 more Smart Citations
“…As will be seen later, SOS1 activity is very important for K + uptake, especially under low-K + conditions. Recently, it has been consistently shown that the difference between tolerant reed and sensitive rice is due to the difference in ability to reduce transport of Na + to the shoot; only the reed plants restricted Na + transport to the shoot base while the rice plants lacked this capacity (Fujimaki et al, 2015). This restriction was shown to involve Na + retrieval from the xylem and recirculation to the soil through the phloem.…”
Section: Resistance To Radial Transport and Xylem Loading Of Na+mentioning
confidence: 99%
“…One such action was shown involving AtHKT1;1-mediated Na + recirculation from the leaf to the root via the phloem (Berthomieu et al, 2003; Horie et al, 2005). Although this means of Na + transport was later found to be either negligible or non-existent (Horie et al, 2007), there is increasing evidence of its occurrence, at least in the root (Tian et al, 2010; Fujimaki et al, 2015). Fujimaki et al (2015) used the positron-emitting tracer imaging system to analyse the direction of movement of radioactive 22 Na + in the roots of reed and rice plants.…”
Section: Regulation Of Toxic Na+ Accumulation In the Leaf Bladementioning
confidence: 99%
See 1 more Smart Citation
“…In rice, sodium in the root continued to migrate to the upper leaves, whereas it moved towards the root tip in a reed. These results suggested that the salt tolerance mechanism of reed maintained a low concentration of sodium in the ground part by returning the sodium absorbed from the root [32]. Positron imaging of zinc has been performed using 62 Zn (t 1/2 = 9.2 hours) [33].…”
Section: Positron Imagingmentioning
confidence: 95%
“…These species are not specialized in using Na for osmoregulation, and excessive Na can disturb their elemental composition homeostasis (Kudo et al, 2010). Some eury-hygro-halophytes species, like Phragmites australis, can transport Na absorbed by upward stream back to the roots, keeping low Na concentrations in the shoots and high Na in the root vacuoles (Fujimaki et al, 2015;Matsushita and Matoh, 1992;Takahashi et al, 2007;Vasquez et al, 2006).…”
Section: Sodium Is the Main Element Of Succulent And Salt-recreting Ementioning
confidence: 99%